PENYULUHAN PEMBUATAN KERUPUK UDANG DI DESA SUNGAI BESAR KECAMATAN KARANG INTAN KABUPATEN BANJAR - Wasdiyanta; Ahmad Baparki; Rohansyah (INSPIRASI: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
This community service was carried out in Sungai Besar Village, Karang Intan District, Banjar Regency with the aim of planning the creation of a shrimp cracker home industry in Sungai Besar Village and providing knowledge about how to make shrimp crackers, by carrying out outreach activities involving members of the Sungai Besar Village community. The service method is provided by means of lectures, questions and answers and simulations. Making Shrimp Crackers is divided into two stages, namely the first part with an introduction to making prawn crackers and the second part regarding the recipe for making prawn crackers